2021
DOI: 10.1186/s43093-021-00087-4
|View full text |Cite
|
Sign up to set email alerts
|

The turn-of-the-month effect in Pakistani stock market

Abstract: This research intends to explore the presence of the “turn-of-the-month-effect (TOME)” in the Pakistani stock market. The TOME is the temporary increase in prices of registered shares on the last operating day of the month and the initial 3–4 days of the following month. The selection incorporates the secondary data, which comprises the ending prices of the “KSE-100 Index” for 2013–2018. Contrary to the previous evidence in Pakistan, we run an in-depth year-wise analysis and report an interesting fact that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The average real return over the last five years for the KSE-100 index is particularly low and even negative mainly because the stock market is quick to reflect changes in political and economic activity and has been deeply affected by the COVID pandemic and other political happenings. This is despite the belief that the Pakistani stock market is considered very resilient and has performed relatively better than the other world markets even during the pandemic (Irtiza et al, 2021). To smooth out the impact of the fluctuations caused by unprecedented external environment factors, even if we compare the Adhyara return with the 20-year average real return of the KSE-100 Index of 16.98%, Adhyara deals still come out at the top.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The average real return over the last five years for the KSE-100 index is particularly low and even negative mainly because the stock market is quick to reflect changes in political and economic activity and has been deeply affected by the COVID pandemic and other political happenings. This is despite the belief that the Pakistani stock market is considered very resilient and has performed relatively better than the other world markets even during the pandemic (Irtiza et al, 2021). To smooth out the impact of the fluctuations caused by unprecedented external environment factors, even if we compare the Adhyara return with the 20-year average real return of the KSE-100 Index of 16.98%, Adhyara deals still come out at the top.…”
Section: Discussionmentioning
confidence: 95%
“…The average real return over the last five years for the KSE-100 index is particularly low and even negative mainly because the stock market is quick to reflect changes in political and economic activity and has been deeply affected by the COVID pandemic and other political happenings. This is despite the belief that the Pakistani stock market is considered very resilient and has performed relatively better than the other world markets even during the pandemic (Irtiza et al. , 2021).…”
Section: Discussionmentioning
confidence: 97%
“…And their study provides new insights into the efficiency of the Indian stock market exchange. Irtiza et al (2021) explored the presence of the turn of the month effect in the Pakistani stock market. Results showed a temporary increase in the prices of registered shares on the last operating day of the month.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent research by Singh et al (2021), found a turn-of-the-month effect on the Stock Market Indices of Brazil, India, and China from January 2000 to 2017, as evidenced by the higher average return in the turn-of-themonth effect period compared to the non-turn of the month effect. Irtiza et al (2021), found a turn-of-the-month effect on the National Stock Exchange and Bombay Stock, where the presence is more robust in companies with small and medium capitalization, and , found a turn-of-the-month effect in the Indian Stock Market Index (NSE).…”
Section: Introductionmentioning
confidence: 99%